Teaching educational technology - Garo, Candelaria D. (Mandaluyong City, Philippines : National Book Store, 2004)
The Youth of today are aptly called computer generation because of their unique orientation to various computer applications. Because computer are in-thing today and looks like they are here to stay, it is incumbent that educational institutions must embrace this trend and make it a part of the teaching-learning process.
Part I. History, meaning and roles of education technology -- Lesson 1. History of educational technology -- Lesson 2. The Meaning of educational technology -- Lesson 3. The Roles and function of educational technology -- Part II. Educational media, identification, production -- Lesson 4. The Cone of experience -- Lesson 5. Pictorial media -- Lesson 6. Visual symbols -- Lesson 7. Audio media -- Lesson 8. The Chalkboard and other display materials -- Lesson 9. Three- dimensional instructional materials -- Lesson 10. The Overhead project (OHP) -- Lesson 11. Computers as aid to teaching -- Lesson 13. The Educational media center.
Includes bibliographical references.
Keywords: EDUCATIONAL TECHNOLOGY